Systematic Review of Development and Content Validity of Patient-reported Outcome Measures in Inflammatory Bowel Disease: Do We Measure What We Measure?. (25th March 2020) - van Andel, Emma M; Koopmann, Brechtje D M; Crouwel, Femke; Noomen, Casper G; de Boer, Nanne K H; van Asseldonk, Dirk P; Mokkink, Lidwine B
Abstract: Background and Aims: Patient-reported outcome measures are increasingly important in daily care and research in inflammatory bowel disease [IBD]. This study provides an overview of the content and content validity of IBD-specific patient-reported outcome measures on three selected constructs. Methods: Databases were searched up to May 2019 for development and/or content validity studies on IBD-specific self-report measures on health-related quality of life, disability, and self-report disease activity in adults. Evidence was synthesised on content validity in three aspects: relevance, comprehensiveness, and comprehensibility following the COnsensus-based Standards for the selection of health Measurement INstruments methodology. Questionnaire items were organised in themes to provide an overview of important aspects of these constructs. Results: For 14/44 instruments, 25 content validity studies were identified and 25/44 measures had sufficient content validity, the strongest evidence being of moderate quality, though most evidence is of low or very low quality. The Crohn's Life Impact Questionnaire and IBD questionnaire-32 on quality of life, the IBD-Control on disease activity, and the IBD Disability Index Self-Report and its 8-item version on disability, have the strongest evidence of sufficient relevance, comprehensiveness, and comprehensibility, ranging from moderate to very low quality. A fair number of recurring items themes, possibly important for the selected constructs, was identified. Conclusions: The body of evidence for content validity of IBD-specific health-related quality of life, self-report disease activity, and disability self-report measures is limited. More content validity studies should be performed after reaching consensus on the constructs of interest for IBD, and studies should involve patients.